PERMASALAHAN YANG DI ALAMI GURU DALAM PROSES PEMBELAJARAN SELAMA MASA PANDEMI COVID 19 DI KAWASAN ACEH BESAR - Maulida Maulida; Irma Aryani (Jurnal Dedikasi Pendidikan, 2022)
Covid 19 has had a huge impact on the world of education. With the emergence of covid 19, the world of education was forced to turn around significantly, the learning process which is usually done face-to-face must be replaced with online learning. The introduction of online learning suddenly has a very long and large effect on the teaching and learning process. Many teachers are not familiar with the online learning process. This research activity was carried out from April 2021 to October 2021. The objects in this study were teachers who teach in high school and junior high schools in the Aceh Besar area. This study uses a quantitative method with a descriptive research approach where the data will be taken using a questionnaire, the sample in this study amounted to 50 teachers. The results showed that the average problem experienced by the teacher was in the "High" category in the aspect of the learning process, which was 84.5%. This is in accordance with the results of the interviews conducted. The teacher admits that it is very difficult to carry out the learning process during the Covid 19 pandemic. The most difficult situation is to equalize the perception of students' abilities